Distribution Optimization Method for Power Environment-Friendly Mixed Insulation Gas - Jie DONG; Bo YANG; Guoxin YI; Haichuan HE; Le MA (Zhongguo dianli)
The state-of-art cost of environmental-friendly SF6/CF4 mixed insulating gas of GIS equipment in the power system is relatively high. In order to ensure its insulation and arc extinguishing performance, SF6 gas is overfilled on site, which is not in line with the purpose of using the mixed gas to achieve environmental protection and prevent liquefaction. Therefore, an optimized method of timed alternate gas blending for environmental-friendly SF6/CF4 mixed insulating gas based on a single mass flow controller is proposed. Through the timed alternate gas blending and instant mixing technology, the gas blending error caused by residual gas in the shared gas pipeline is analyzed and optimized. The SF6 gas output time correction technology and the time reallocation method for the last period are studied, further reducing the error in the mixing ratio of the filled gas. Simulation experiments show that the deviation of the instantaneous mixing ratio and the mixing ratio after 24 hours from the target value is less than ±0.5%, which meets the requirements of DL/T 2243—2021 standard.